All-Optical Wavelength Multicasting in Quadruple Resonance-Split Coupled Silicon Microring Cavity - Awanish Pandey; Shankar Kumar Selvaraja (IEEE Photonics Journal)
We demonstrate an all-optical four-channel wavelength multicasting in a coupled silicon microring resonator system. The scheme is based on two-photon-absorption-induced free carrier dispersion in silicon. The coupled cavity facilitates resonance splitting that is utilized as individual channels for multicasting. Using the split resonances, we achieve an aggregate multicasted data rate of 48 Gbps (4 × 12 Gbps). Moreover, we also present a detailed analysis and performance of the multicasting architecture using bit error rate and eye diagram measurements.